2005
DOI: 10.1111/j.1745-7254.2005.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere and telomerase as targets for anti-cancer and regeneration therapies

Abstract: Telomerase is a ribonucleoprotein that directs the synthesis of telomeric sequence. It is detected in majority of malignant tumors, but not in most normal somatic cells. Because telomerase plays a critical role in cell immortality and tumor formation, it has been one of the targets for anti-cancer and regeneration drug development. In this review, we will discuss therapeutic approaches based mainly on small molecules that have been developed to inhibit telomerase activity, modulate telomerase expression, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Telomerase is a ribonucleoprotein reverse transcriptase that is suppressed in normal somatic cells and is activated in cancer cells and immortalized cell lines (28). hTERT acts as a limiting factor for TA.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase is a ribonucleoprotein reverse transcriptase that is suppressed in normal somatic cells and is activated in cancer cells and immortalized cell lines (28). hTERT acts as a limiting factor for TA.…”
Section: Discussionmentioning
confidence: 99%
“…Although some tumors activated a yet unknown alternative mechanism of telomere extension, the majority (>90%) of human cancer cells acquire immortality by expression of the hTERT. It has been shown that hTERT expression is regulated at the transcriptional level, thereby providing a promising tool for tumor-specific gene expression (16,17).…”
mentioning
confidence: 99%
“…Accumulation of p53 protein in the nucleus induces a variety of downstream signaling pathways that mediate cellular responses to stress [5,14,19]. Therefore, p53 plays a crucial role in controlling cellular fate after irradiation [13,19].…”
Section: Discussionmentioning
confidence: 99%
“…Telomeres are specialized structures at the chromosome ends that are composed of TTAGGG repeated sequences, which interact with specific proteins and provide the protective caps of linear chromosomes [14]. The main functions of telomeres are to protect chromosome ends from deleterious DNA repair or recombination events and maintain the stability of the chromosome [5].…”
Section: Introductionmentioning
confidence: 99%